2020
DOI: 10.1155/2020/4037639
|View full text |Cite
|
Sign up to set email alerts
|

A Five-Gene Signature for Recurrence Prediction of Hepatocellular Carcinoma Patients

Abstract: Background. Hepatocellular carcinoma (HCC) is one of the most aggressive malignancies with poor prognosis. There are many selectable treatments with good prognosis in Barcelona Clinic Liver Cancer- (BCLC-) 0, A, and B HCC patients, but the most crucial factor affecting survival is the high recurrence rate after treatments. Therefore, it is of great significance to predict the recurrence of BCLC-0, BCLC-A, and BCLC-B HCC patients. Aim. To develop a gene signature to enhance the prediction of recurrence among HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The joint analysis of Arjun Sarathi and Ashok Palaniappan showed that there were different stage-specific genes in different AJCC stages of HCC, specifically, they identified 2 genes specific to stage I and II, 10 specific to stage III, and 35 specific to stage IV 25 . Recently, a five-gene predictive signature was developed and highlighted potential prediction feasibility of recurrence of early-stage HCC 26 . In our work, 3623 DEGs between C1 and C2 subtypes were identified, and a risk score was constructed using univariate Cox analysis and LASSO-Cox regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The joint analysis of Arjun Sarathi and Ashok Palaniappan showed that there were different stage-specific genes in different AJCC stages of HCC, specifically, they identified 2 genes specific to stage I and II, 10 specific to stage III, and 35 specific to stage IV 25 . Recently, a five-gene predictive signature was developed and highlighted potential prediction feasibility of recurrence of early-stage HCC 26 . In our work, 3623 DEGs between C1 and C2 subtypes were identified, and a risk score was constructed using univariate Cox analysis and LASSO-Cox regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, machine learning methods have also been used to predict liver cancer recurrence. Wang et al( Wang et al, 2020 ) used lasso and Cox regressions to screen five mRNAs to predict HCC recurrence, and the predicted AUC values for 1-year, 2-year, and 3-year RFS rates from the independent validation data were 0.752, 0.651, and 0.677, respectively. Iizuka et al( Iizuka et al, 2003 ) used Fisher’s linear classifier algorithm to predict intrahepatic recurrence in hepatocellular carcinoma patients within 1 year after resection, using 18 mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The Kaplan-Meier (K-M) survival analysis was conducted using the R package "survival". The timedependent relative operating characteristic (ROC) curve was used to assess the accuracy of the established model, calculated with the R package "survival ROC" [7] . Concordance index (C-index) values were calculated based on Harrell's C-index [17] , to evaluate the difference between predicted value and actual value of Cox model in survival analysis and judge the prediction accuracy of the prognostic model of tumor patients.…”
Section: Evaluation Of the Value Of The Risk Scoring Modelmentioning
confidence: 99%
“…The mitochondria produce adenosine triphosphate (ATP) for cells. Recent studies have shown that mitochondria regulate various physiological and pathological functions, such as the initiation, progression and metastasis of tumor cells [6][7] . The mitochondria produce reactive oxygen species (ROS) in the cell.…”
Section: Introductionmentioning
confidence: 99%